2011
DOI: 10.1117/12.898025
|View full text |Cite
|
Sign up to set email alerts
|

Development and fabrication of a hyperspectral, mirror based IR-telescope with ultra-precise manufacturing and mounting techniques for a snap-together system assembly

Abstract: We report on an ultra-precise manufacturing method of a hyperspectral, mirror based IR-Telescope for applications in the Mid-wavelength infrared (MWIR). The proposed method simplifies the otherwise time consuming system alignment by the use of a snap-together assembly technique, that can be used for rotationally symmetric designs such as Korsch or Three Mirror Anastigmatic (TMA) telescope designs. The proposed technology is based on diamond machining of at least two mirror surfaces on one common substrate in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Tolerances between mounting features and the optical element in the µm-range, arc second-range respectively are mandatory for a simplified optics alignment. Risse et al 18 demonstrated a "snap-together" assembly of a IR mirror telescope with diffraction limited performance based on this approach.…”
Section: Alignment Of the Point Cloudmentioning
confidence: 98%
“…Tolerances between mounting features and the optical element in the µm-range, arc second-range respectively are mandatory for a simplified optics alignment. Risse et al 18 demonstrated a "snap-together" assembly of a IR mirror telescope with diffraction limited performance based on this approach.…”
Section: Alignment Of the Point Cloudmentioning
confidence: 98%
“…Furthermore, optical and mechanical reference structures on the mirrors may be manufactured in the same SPDT run. This strategy allows for a significantly simplified adjustment of the optical system [11,12]. The respective duolith mirrors of the DESIS instrument are depicted in Fig.…”
Section: A Mirror Designmentioning
confidence: 99%
“…These elements will be finished by single-point diamond fly-cutting [11,12] in a single machining run. They will be used to define a high precision starting point for the adjustment of the mirrors.…”
Section: B Instrument Housingmentioning
confidence: 99%
“…Metal optics has proven to be advantageous in respect of using conventional CNC and ultra-precision fabrication methods to realize complex and light-weighted instrument structures. Moreover, the mirror designs can be effectively optimized for a deterministic system assembly and optimization [2]. Limitations in terms of dimensional stability over temperature and time are mainly given by the inherent material properties (figures of merit) of the substrate material in interaction with the polishing layer.…”
Section: Introductionmentioning
confidence: 99%